Sibling rivalry: Are gender differences or age ranges of birth the cause of social jealousy - Kamil, Nurhusni; Narjis, Khalilah; Sope, Yuanita Anthon (INTERNATIONAL JOURNAL OF CHILD AND GENDER STUDIES, 2024)
A little competition created between siblings is normal throughout the life span. This shows that the closeness between the two is close enough to give rise to many problems, although in the end, sibling rivalry will disappear over time when each child reaches adulthood. Sibling rivalry starts in childhood. Every child who is not born as an only child will know about sibling rivalry. Sibling rivalry causes several changes in behaviour in a more negative direction. One of the negative attitudes produced by children is social jealousy between siblings, which results in sudden and unusual changes in behaviour. This research aims to find out and identify the factors that cause sibling rivalry in sibling relationships based on gender differences and birth age ranges. The type of research used in this research is qualitative research with a case study approach. The sample used in this study was eight children with classifications, namely, four children of the same gender and four children of the opposite gender. The data collection technique used was in-depth and unstructured interviews submitted to each parent. For data analysis techniques, Miles and Huberman analysis include data reduction, data display, and conclusion drawing and verification. The results of this study show that birth age is a factor that causes sibling rivalry between sibling relationships, based on the sample that has been studied.